Change in Proteolytic Profile in Heifers After Oligofructose Overload - Li, Shuaichen; Zheng, Xiaoyan; Ding, Mengyuan; Tao, Ze; Zhang, Jiantao; Zhang, Na (Frontiers in Veterinary Science, 2020)
Laminitis in cattle is an important underlying cause of lameness, which leads to a significant reduction in economic and animal welfare. Nevertheless, the disordered physiological processes of laminitis remain unclear. Several proteinases are probably involved in the disorder of basement membrane (BM) metabolism in laminitis, for instance, matrix metalloproteinases (MMPs), neutrophil elastase (NE), and myeloperoxidase (MPO). This study aimed to investigate the change in proteolytic profile in circulating and lamellar tissues using an oligofructose (OF) overload-induced laminitis model in heifers. Twelve clinically healthy and nonlame Chinese Holstein heifers were recruited and randomly divided into two groups: OF-induced and control (CON). The OF-induced heifers group (n = 6) was administered 17 g/kg of body weight (BW) of OF dissolved in 2 L/100 kg of BW of tap water via the oral-rumen tube. The CON group (n = 6) was given an equal volume of tap water. The plasma samples were collected 0, 6, 12, 18, 24, 36, 48, 60, and 72 h after administration, and the lamellar samples were collected 72 h after euthanasia. The plasma samples were analyzed by zymography and reverse zymography. Histological examination, zymography, reverse zymography, and Western blot of lamellar samples were conducted. In the plasma of the OF-induced group, the pro-MMP9 activity increased from 36 h (P < 0.001) to 60 h (P < 0.05). Moreover, the plasma tissue inhibitors of metalloproteinase 1 (TIMP1) activity decreased after 18 h (P < 0.05), while the ratio of pro-MMP9 to TIMP1 and TIMP2 increased after 18 h (P < 0.001) and 48 h (P < 0.05), respectively. The act-MMP2, pro-MMP9, and act-MMP9 activities increased in the lamellar tissue of the OF-induced group compared with the CON group (P < 0.05). In addition, the expression of lamellar NE protein was higher in the OF-induced group (P < 0.01), while no change was found in lamellar MPO protein compared with the CON group. In conclusion, increased pro-MMP9 combined with decreased TIMP1 activity in the circulation might have caused the activation of blood neutrophil, while the activation of proteolytic enzymes in lamellar probably led to the dysfunction of BM in the